THE PRINCIPLE OF ACCURACY IN FAMOUS TRADEMARK REGISTRATION: AN ANALYSIS OF COURT RULING NUMBER 36/PDT.SUS-MEREK/2024/PN.NIAGA.JKT.PST - Arifin, Azzahra; Joesoef, Iwan Erar (JCH (Jurnal Cendekia Hukum), 2024)
The trademark registration system in Indonesia, namely First to File, is often misused by unscrupulous individuals to register trademarks similar to well-known brands. This study aims to analyze and address issues related to trademark registration in Indonesia, including the First to the File system in trademark registration, primarily based on the “Jollibee vs Jollybe” trademark dispute, by integrating the use of one of the General Principles of Good Governance (AUPB), namely the principle of accuracy. Implementing AUPB can reduce the potential for conflicts and trademark disputes in the future. This study uses a statute approach by prioritizing primary and secondary data sources collected through literature research and uses qualitative descriptive analysis techniques. The results of this study indicate that the First to File system in trademark registration in Indonesia only provides legal protection after the Trademark is registered. Therefore, applying the Principle of Care in AUPB as a guideline in the trademark registration process is essential. However, suppose there is an error made by the trademark examiner when registering a trademark. In that case, it can be accounted for by creating a report addressed to the Indonesian Ombudsman to obtain mediation, consolidation, or adjudication.